Real world neural networks for interactive music composition in real time - Bickerstaffe, Colin (2017)
A new model designed for musicians to use as a tool for practicing and improvisation is developed based on a corpus of Jazz lead sheets. It is lightweight enough to work within the CPU and memory constraints of consumer equipment and operate in real time with input from a standard midi device. The model is also compatible for use on a Raspberry Pi for ultimate portability (at the cost of a significantly longer training time).